Implementasi Pendidikan Agama Islam dalam Membangun Soft Skill Siswa: The Implementation of Islamic Religious Education in Developing Students’ Soft Skills - Huroniyah, Fuadatul (LP2M UIN KH.Achmad Siddiq Jember, 2009)
-